Good University Governance on Higher Education Performance - Ainun Nisak, Nuril; Yuniarti, Rina; Hernadianto, Hernadianto; Sumarlan, Ahmad (Universitas Veteran Bangun Nusantara Sukoharjo, 2025)
Good University Governance is the concept of good university management. GUG is a higher education governance system that applies the principles of good governance. This study aims to determine the effect of Good University Governance on the performance of Muhammadiyah and Aisyiyah universities in Sumatra. This research is a quantitative research with primary. The population in this study were Muhammadiyah and Aisyiyah Universities throughout Sumatra. And the research sample was 35 samples and 36 populations of Muhammadiyah and Aisyiyah Universities in Sumatra. The data analysis technique used in this study is purposive sampling census using SPSS version 22. The results of this study indicate that Good University Governance has effect on the performance of Muhammadiyah and Aisyiyah Universities in Sumatra while I has an effect on the performance of Muhammadiyah and Aisyiyah Universities in Sumatra. Therefore, with the results of this study, it can be a reference material to be able to improve the implementation of good university governance in Muhammadiyah and Aisyiyah Universities in particular and other universities in general. Increasing good university governance will improve college performance for that, college management and stakeholders as well as the government must make efforts to improve the implementation of good university governance in one college.